2020
DOI: 10.1007/978-3-030-63319-6_15
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Simulation of Steady Natural Convection in an H-Form Cavity

Abstract: The simulation of natural convection problem based on the Galerkin finite-element method, with the penalty finite-element formulation of the momentum balance equation, is exploited for accurate solutions of equations describing the problem of H-Form cavity differentially heated side walls. The cavity is occupied by the air whose Prandtl number is Pr=0.71, the fluid is assumed to be steady, viscous and incompressible within thermal convection. A numerical investigation has been made for Rayleigh numbers ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Similar research was conducted by Keramat et al [ 19 ] regarding free convection in an H -shaped chamber filled with air and containing porous fins. Loukili et al [ 20 ] studied the free convective flow of air within an H -shaped chamber using the Galerkin finite element approach. They demonstrated that higher interior heights resulted in less efficient heat transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar research was conducted by Keramat et al [ 19 ] regarding free convection in an H -shaped chamber filled with air and containing porous fins. Loukili et al [ 20 ] studied the free convective flow of air within an H -shaped chamber using the Galerkin finite element approach. They demonstrated that higher interior heights resulted in less efficient heat transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The applications of H -shaped chambers in thermal and fluid engineering have garnered significant attention in the existing literature, as evidenced by numerous studies [ [16] , [17] , [18] , [19] , [20] , [21] ]. Despite the extensive research on H -shaped chambers, a critical gap exists in exploring entropy production resulting from MHD free convection within such chambers, particularly when considering the variable dimensions and the impact of Joule heating.…”
Section: Introductionmentioning
confidence: 99%
“…However, the optimal states (parallel flow) can only be achieved by calculating straight sections of pipeline without the obstacles using the hexahedral cells [30]. The direction of the flow is always in the general direction with respect to the cell walls (hexahedral, tetrahedral, and polyhedral) in the most flows [31].…”
Section: Introductionmentioning
confidence: 99%